RESPON PERTUMBUHAN PUERARIA JAVANICA TERHADAP DOSIS RHIZOBIUM SP. PADA BEBERAPA JENIS TANAH YANG BERBEDA - Ari Selfandi; Ryan Firmansyah; Pauliz Budi Hastuti (AGROISTA : Jurnal Agroteknologi, 2021)
This study aims to determine the growth response of Pueraria javanica to Rhizobium sp. doses on different soil types. This research was conducted in the local community garden located in Maguwoharjo Depok District, Sleman Regency, D. I. Yogyakarta at an altitude of 118 Meters Above sea level. The research method used is factorial with a complete randomized design (RAL). The first factor is the dose of Rhizobium sp. sp. consists of 4 levels, namely 0 g (control), 5 g, 10 g, and 15 g. The second factor is the type of soil consisting of 3 levels, namely regosol, latosol, and grumosol. The results showed interaction between the dose of Rhizobium sp. with different types of soil against the best plant height in the soil type grumusol with various doses of Rhizobium sp. and the best dry root weight in the soil type grumusol with a dose of Rhizobium sp. 10 g. Rhizobium sp. dose gives the same effect on the growth of Pueararia javanica in number of leaves, fresh weight of header, dry weight of header and number of root, except at fresh root weight. Kata kunci : Pueraria javanica, Rhizobium sp., regosol, latosol, grumusol